The Power of Language: Gender, Status, and Agency in Performance Evaluations. - Smith, David G.; Rosenstein, Judith E.; Nikolov, Margaret C.; Chaney, Darby A. (Sex Roles, 2019)
In the workplace, women often encounter gender stereotypes and biases that reinforce the existing gender hierarchy, may hinder women's career aspirations and retention, and may limit their ability to be promoted—especially in traditionally male organizations. Long-standing and widely held (although often unconscious) beliefs about gender can reinforce women's perceived lower status position relative to men's. Because men are described/prescribed as agentic (often masculine) and women as communal (often feminine), women leaders are often evaluated as being status-incongruent. We explore the gendered assignment of leader attributes with particular attention to associations of agentic competence (deficiency for women) and agentic dominance (penalty for women). We examined peer evaluations of 4344 U.S. Naval Academy students who are assigned attributes from a predefined list. Although men and women received similar numbers of descriptive (positive) attributes, women received more proscriptive (negative) attributes than did men and these individual attributes were predominantly feminine. These findings offer evidence that women leaders' status incongruity may be associated with perceived competence (agentic deficiency). A contribution of our analysis is theory testing using data from a real-life performance evaluation system. Additionally, our research contributes to our knowledge of gendered language and status characteristics in performance evaluations and can assist researchers and practitioners with developing interventions. Understanding the association of gender status beliefs with evaluation processes may facilitate changing workplace culture to be more gender-inclusive through less biased and stereotypical performance evaluations.